Analgesic effect of honey bioactive compounds and its role in reducing morphine tolerance - Khamsah Suryati, Mohd; Nasir, Mohamad; Nor Hidayah, Abu Bakar (Open Science Publishers LLP Inc., 2015)
Honey has been used as a supplement nutrient in human for centuries. It exerts antibacterial, anticancer, anti-inflammatory properties as well as analgesic activity. But not many studies have been done to analyze effect of honey on morphine tolerance. Hence, this review is targeting on analgesic effect of honey bioactive compounds and their potential in morphine tolerance study.